Pengaruh Faktor-Faktor Kualitas, Nilai, dan Preferensi Merek terhadap Loyalitas Konsumen pada Produk Bromen - Sudi, Didih Muhamad; Purwadi, Anto; Firmansyah, Alfian (Jurnal EMT KITA, 2024)
This research investigates the influence of perceived quality, perceived value, brand preference, and consumer satisfaction on consumer loyalty for Bromen products. The research method involves multiple regression analysis using multiple linear regression measuring instruments. The results of the validity and reliability tests show that all research variables are reliable and valid. Regression analysis reveals that perceived value and brand preference significantly influence consumer loyalty, with contributions of 18.8% and 25.3%. Even though perceived quality and consumer satisfaction make a positive contribution, both are not statistically significant. The coefficient of determination of 18.8% shows that variations in consumer loyalty can be explained by these four factors. The implications of this research underline the importance of companies increasing brand preference through intensive marketing strategies and adding added value to products to strengthen perceived value, while still paying attention to perceived quality and consumer satisfaction to strengthen consumer loyalty.